Water parameters, nutrient, and gas samples in the Coffs Creek estuary, 2017-2018 - Rebecca Woodrow (PANGAEA, 2021)
Longitudinal monthly surveys were performed on eleven occasions from July 2017 to June 2018. A total of 66 samples were collected over a total period of 12 months. Water parameters, nutrient, and gas samples were taken approximately every month (excluding September 2017) from the upper water column at 6 sites along the creek salinity gradient at low tide, from the estuary extquotesingles mouth, and to the upper freshwater creek. A calibrated YSI EC300A was used to measure salinity (±0.02), whilst a calibrated Hach HQ40D measured DO (±0.2 mg/L) and water temperature (±0.10°C). Nutrient samples (including duplicates), filtered and unfiltered, were collected with a sample-rinsed 60 mL polyethylene syringe. Samples for dissolved organic carbon (DOC) analysis were filtered using pre-combusted 0.7 μm GF/F filters (Whatman), into 40 mL borosilicate vials (USP Type I). Samples for nitrogen were immediately filtered using Satourious ™ 0.45μm cellulose acetate syringe filters into 10 mL polyethylene sample tubes. All samples were kept in a cold icebox, away from light, for less than 5 hours and then frozen until laboratory analysis. Nutrient analysis of DOC was performed with the 40 mL borosilicate vials (USP Type I) first treated with 30 μL of H3PO4 before analysis using an Aurora 1030W TOC Analyser (Thermo Fisher Scientific, ConFLo IV). Nutrient analysis of ammonium (NH4+), NOx (nitrate plus nitrite), and total dissolved nitrogen (TDN) was performed on the 10 mL polyethylene sample tubes colourimetrically using a Lachat Flow Injection Analyser. N2O samples were obtained directly from the creek with two replicate 250 mL borosilicate bottles, filled from 200.167emcm below the surface, ensuring zero headspace, and then immediately treated with 200 μL of HgCl2 solution and capped. The borosilicate bottles were taken to the laboratory for gas extraction where the bottle was inverted to add 60 mL of zero-air (of known N2O concentration) headspace using a needlepoint syringe while simultaneously extracting 60 mL of sample, before being shaken for 4 minutes. Next, 60 mL of gas was extracted from the bottle, while 60 mL of sample was replaced. The subsequently extracted gas was transferred to a gasbag and diluted with 200 mL of known N2O concentration zero-air ready for analysis. The gasbags were analysed using cavity ringdown spectroscopy on a calibrated Picarro G2308. The same measurements of water parameters of temperature, dissolved oxygen and salinity and nutrient samples of dissolved organic carbon, filtered and unfiltered nitrogen and nitrous oxide were collected through time series apparatus, hourly and 3 hourly, over 185 hours and exclusively at one site in the lower estuary (Site 1). A calibrated Hydrolab MS5 sonde measured and logged water temperature (±0.02°C), DO (±0.2 mg/L), and salinity (±0.02) at 30 m intervals and a depth logger (CTD diver) measured water depth in 15-minute intervals. Nutrient samples were collected and analysed as in the longitudinal monthly surveys. N2O samples were collected from a time series gas equilibration device via a one-way valve into 150 mL syringes then transferred from the syringes into a Supelco company 1 L gasbag. A total of 800 mL of gas was taken per sample. The gasbags were analysed for N2O using cavity ringdown spectroscopy on a calibrated Picarro G2308. Total dissolved nitrogen and dissolved inorganic nitrogen were calculated from the nitrogen samples.